Evaluation of pharmaceutical interventions according to drug related problems in the hospital setting. Issue 2 (12th March 2012) - Afonso, R.; Prata, A.; Elias, C.; Costa, C.; Teixeira, S.; Neta, S.; Oliveira, M.; Oliveira, I.; Brito, A.; Frade, P.; Almeida, P.; Badracim, N.; et al.
Abstract : Background: Pharmaceutical Interventions (PI) are part of pharmaceutical care process and aim to reduce drug-related negative results through early detection of drug related problems (DRP). They are mainly focused on renal/hepatic adjustment of drugs, and supervision of medicines with narrow therapeutic windows and unconventional regimen features. Purpose: Evaluation of PI in separate departments during the first semester of 2011. This will allow a consistent and uniform record and classification of PI, aiming to raise doctors' awareness for the most frequent prescription-related DRPs. Materials and methods: PI's were recorded on a database (Excel 2007) and classified according to the DÁDER method (Third Revision 2005-University of Granada), accepted as a tool to identify DRPs. DRPs are classified according to: Need: DRP1-Need of additional treatment and DRP2-Unnecessary drug; Efficacy: DRP3-Non-quantitative lack of efficacy and DRP4-Quantitative lack of efficacy; Safety: DRP5-Non-quantitative insecurity and DRP6-Quantitative insecurity. Results: From a total of 1835 PI, 82% were accepted (AC). The DRP's distribution was: DRP1-17, 4%, DRP2-25, 4%, DRP3-2%, DRP4-16, 1%, DRP5-5, 1%, DRP6-33, 5%. Departments were analysed separately because of different specifications. The medicine department had a total of 795 PI, with an acceptance of 80, 4%. The most frequent DRP's were DRP6 (38%), DRP1 (20%) and DRP2 (19%). The surgical department had 470 PI, with an acceptance of 95, 5%. The most frequent DRP's were DRP2 (42, 2%), DRP6 (19, 9%), DRP1 (18, 6%) and DRP4 (17, 2%). Intensive care units had a total of 149 PI with 89, 3% accepted, the most frequent being DRP6 (40, 4%) and DRP4 (31, 5%). The emergency department had a total of 421 PI with 67% accepted. The most frequent DRP's were DRP6 (37%) and DRP2 (24%). Conclusions: This analysis showed that: ▶ The pharmaceutical interventions had high rates of acceptance (≥80%) ▶ The most frequent DRP were related to quantitative insecurity (DRP6), followed by the prescription of unnecessary drug (DRP2), despite some differences between different departments.